Assessment of the Impact of Petroleum Depot Effluents on a Nearby River Quality - Nasir Abdus-Salam; Olamide Sodiq Ademola; Mojeed Olalekan Bello (European Scientific Journal, ESJ, 2017)
The possible effects of the petroleum depot effluents on the river water quality were examined. Twelve-monthly water sampling (June, 2015 to May, 2016) were taken from upstream and downstream of the river. Physicochemical parameters such as pH, temperature, turbidity, total dissolved solid (TDS), total suspended solid (TSS), total solid (TS), biochemical oxygen demand (BOD), dissolved oxygen (DO), total alkalinity, electrical conductivity (EC), total hardness, phosphate, sulphate, nitrate, chloride and heavy metals were determined using standard methods. The pH, temperature, TDS, TSS, TS, BOD, total alkalinity and chloride concentrations exceeded the guidelines values of WHO, SON and EPA during the dry season and within the permissible limits during the rainy season. The EC, total hardness, sulphate and nitrate were within the range of standards while phosphate and turbidity exceeded the permissible standard values throughout the sampling period. Pearson correlation coefficient of ions showed that there was a significant correlation at the 0.01 probability level. Therefore, the metals and anions are from a common source. Atomic Absorption Spectrophotometric results showed that concentration of Cd and Ni exceeded standard values, 0.005 and 0.1 mg/L respectively during the dry season while Pb and Cr exceeded the permissible limits, 0.01 and 0.05 mg/L during the rainy season. Copper was within the permissible limit 0.5 mg/L while Zn exceeded the permissible limit 0.05 mg/L throughout sampling periods. The levels of Pb, Cd, Zn, Ni, and Cr in the river are particularly high enough to cause public concerns.